A Prospective, Randomized Phase II Study of Adjuvant Gemcitabine Versus S-1 After Major Hepatectomy for Biliary Tract Cancer (KHBO 1208): Kansai Hepato-Biliary Oncology Group. Issue 2 (August 2019) - Kobayashi, Shogo; Nagano, Hiroaki; Tomokuni, Akira; Gotoh, Kunihito; Sakai, Daisuke; Hatano, Etsuro; Seo, Satoru; Terajima, Hiroaki; Uchida, Yoichiro; Ajiki, Tetsuo; Satake, Hironaga; Kamei, Keiko; et al.
Abstract : Objective: To evaluate each arm independently and compare adjuvant gemcitabine (GEM) and S-1 chemotherapy after major hepatectomy (hemihepatectomy or trisectionectomy) for biliary tract cancer (BTC). Background: Standardized adjuvant therapy is not performed after major hepatectomy for BTC, and we determined the recommended dose in the former study (KHBO1003). Methods: We performed a multicenter, randomized phase II study. The primary measure was 1-year recurrence-free survival (RFS); the secondary measures were other RFS, overall survival (OS), and others. The following 6-month adjuvant chemotherapy was administered within 12 weeks of R0/1: GEM (1000 mg/m 2 ) every 2 weeks; or S-1 (80 mg/m 2 /d) for 28 days every 6 weeks. Thirty-five patients were assigned to each arm (alpha error, 10%; beta error, 20%). Results: No patients were excluded for the per-protocol analysis. There were no statistically significant differences in the patient characteristics of the 2 arms. The 1-year RFS and 1-year OS rates of the GEM arm were 51.4% and 80.0%, respectively, whereas those of the S-1 group were 62.9% and 97.1%. The comparison of the 2 arms revealed that 2-year RFS rate, 1 and 2-year OS rates, and OS curve of the S-1 arm were superior to GEM. With regard to OS, the hazard ratio of the S-1 group was 0.477 (90% confidence interval 0.245–0.927). Conclusion: The comparison of the survival of the 2 groups revealed that adjuvant S-1 therapy may be superior to adjuvant GEM therapy after major hepatectomy for BTC.